Analisis Faktor-Faktor yang Mempengaruhi Profitabilitas - Sitepu, Rafi Ashari; Djazuli, Atim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Return on assets (ROA) of Bank Sinarmas Sharia Business Unit has a low performance. This type of research is explanatory research (explanatory research). The collection of data used in this study is to use documentation techniques, namely the financial statements of the company PT. Bank Sinarmas Sharia Business Unit 2012 – 2021. The data analysis technique used in this study is the classical assumption test, multiple linear regression analysis, coefficient of determination, t test and F test. The results of this study indicate that the Capital Adequacy Ratio (CAR) has a positive effect and significant to the profitability of Bank Sinarmas Sharia Business Unit, Operating Expenses Operating Income (BOPO) has a negative and significant effect on the profitability of Bank Sinarmas Sharia Business Unit, Non-Performing Financing (NPF) has a negative and significant effect on the profitability of Bank Sinarmas Sharia Business Unit, Financing Deposit Ratio (FDR) has no significant effect on the profitability of Bank Sinarmas Sharia Business Unit. Capital Adequacy Ratio (CAR), Operating Expenses for Operating Income (BOPO), Non-Performing Financing (NPF), and Financing Deposit Ratio (FDR) significantly affect the profitability of the Bank. Sinarmas Sharia Business Unit. Abstrak Return on asset (ROA) Bank Sinarmas Unit Usaha Syariah memiliki kinerja yang rendah. Jenis penelitian ini adalah explanatory research (penelitian penjelasan). Pengumpulan data yang digunakan pada penelitian ini adalah menggunakan teknik dokumentasi, yaitu laporan keuangan perusahaan PT. Bank Sinarmas Unit Usaha Syariah Tahun 2012 – 2021. Teknik analisis data yang digunakan pada penelitian ini adalah uji asumsi klasik, analisis regresi linier berganda, koefisien determinasi, uji t dan uji F. Hasil penelitian ini menunjukkan bahwa Capital Adequacy Ratio (CAR) berpengaruh positif dan signifikan terhadap profitabilitas Bank Sinarmas Unit Usaha Syariah, Beban Operasional Pendapatan Operasional (BOPO) berpengaruh negatif dan signifikan terhadap profitabilitas Bank Sinarmas Unit Usaha Syariah, Non Performing Financing (NPF) berpengaruh negatif dan signifikan terhadap profitabilitas Bank Sinarmas Unit Usaha Syariah, Financing Deposit Ratio (FDR) tidak berpengaruh signifikan terhadap profitabilitas Bank Sinarmas Unit Usaha Syariah. Capital Adequacy Ratio (CAR), Beban Operasional Pendapatan Operasional (BOPO), Non Performing Financing (NPF), dan Financing Deposit Ratio (FDR) berpengaruh secara signifikan terhadap profitabilitas Bank Sinarmas Unit Usaha Syariah.